Simvastatin aggravates impaired autophagic flux in NSC34-hSOD1G93A cells through inhibition of geranylgeranyl pyrophosphate synthesis. (15th June 2019) - Qi, Weijing; Yan, Lina; Liu, Yaling; Zhou, Xiaomeng; Li, Rui; Wang, Yafei; Bai, Lin; Chen, Juan; Nie, Xiangyu
Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by selective loss of motor neurons. Statins are widely used as cholesterol-lowering drugs and significantly reduce the risk of cardiovascular and cerebrovascular diseases. Increasing evidence indicates the protective effects of statins against certain neurodegenerative diseases. However, in ALS, many studies have found that statins might accelerate disease progression and shorten survival, although the exact mechanism is unclear. In the present study, we investigated the effect of simvastatin on NSC34cells stably transfected with the G93A mutation in human SOD1 (NSC34-hSOD1G93A cells), a recognized in vitro model of ALS. Our results showed that simvastatin caused a decrease in cell viability and the accumulation of autophagic vacuoles with elevated levels of LC3 II/I and P62 in NSC34-hSOD1G93A cells. Conversely, these outcomes were completely reversed by co-incubation with mevalonate, farnesyl pyrophosphate (FPP) or geranylgeranyl pyrophosphate (GGPP) but not cholesterol. In addition, inhibition of geranylgeranyl transferase I by GGTI-286 led to similar alterations in cell viability and autophagic marker levels. These results indicated that the cytotoxic effect of simvastatin on NSC34-hSOD1G93A cells might be due to the aggravation of autophagic flux impairment through the inhibition of GGPP synthesis. Highlights: Simvastatin decreased NSC34-hSOD1G93A cell viability in a dose- and time-dependent manner. Simvastatin aggravated impaired autophagic flux in NSC34-hSOD1G93A cells. These effects of simvastatin were related to the inhibition of geranylgeranyl pyrophosphate synthesis.